2018
DOI: 10.1002/wrna.1501
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase‐3 and alternative splicing

Abstract: Glycogen synthase kinase-3 (GSK-3) is a highly conserved negative regulator of receptor tyrosine kinase, cytokine, and Wnt signaling pathways. Stimulation of these pathways inhibits GSK-3 to modulate diverse downstream effectors that include transcription factors, nutrient sensors, glycogen synthesis, mitochondrial function, circadian rhythm, and cell fate. GSK-3 also regulates alternative splicing in response to T-cell receptor activation, and recent phosphoproteomic studies have revealed that multiple splici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 159 publications
2
16
0
Order By: Relevance
“…The catalytically active regions of these two subtypes exhibit 97% sequence homology. Furthermore, GSK-3alpha and GSK-3beta are widely expressed in cells and tissues and have similar biological characteristics [45]. Recent studies have found that GSK-3beta can phosphorylate many endogenous substrates, including numerous proteins and transcription factors involved in metabolism.…”
Section: Akt Target Proteinsmentioning
confidence: 99%
“…The catalytically active regions of these two subtypes exhibit 97% sequence homology. Furthermore, GSK-3alpha and GSK-3beta are widely expressed in cells and tissues and have similar biological characteristics [45]. Recent studies have found that GSK-3beta can phosphorylate many endogenous substrates, including numerous proteins and transcription factors involved in metabolism.…”
Section: Akt Target Proteinsmentioning
confidence: 99%
“…With more than 40 definitely identified targets and more than 500 proposed candidate substrates, GSK3 is involved in the regulation of a plethora of intracellular/molecular, organic/cellular, and (patho-)physiological events [1]. For instance, GSK3 has an influence on transcriptional regulation, alternative splicing [2,3], and mRNA stability [4]. On the protein level, GSK3 affects translation and protein synthesis [5,6], protein activity, localization, and degradation [7] (including its participation in the β-catenin destruction complex [8]).…”
Section: Introductionmentioning
confidence: 99%
“…GSK3 contributes to the regulation of many proteins implicated in a wide range of cellular functions [11][12][13][14] . Which GSK3 substrate(s) may be most relevant to the mood and cognitive enhancing properties of GSK3 inhibition by lithium remains unclear and none have been unambiguously associated with the mood and cognitive enhancing properties of GSK3β inhibition.…”
Section: Introductionmentioning
confidence: 99%